Hydrogenation catalyst and its preparation method and application
By combining polyimide/silicon-containing alumina composite support with active metal components, a metal-semiconductor heterojunction is formed, which solves the problem of reduced catalytic efficiency caused by agglomeration of metal particles and interaction between metal and support in existing hydrogenation catalysts, and achieves efficient residual hydrotreatment.
Patent Information
- Application Number
- CN202210448716.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-04-26
AI Technical Summary
Existing hydrogenation catalysts are prone to agglomeration or uneven distribution of metal particles when they are loaded with high metals, and the strong interaction between metal and support during calcination leads to a reduction in catalytic efficiency.
The polyimide/silicon-containing alumina composite support is combined with the active metal component, and the semiconductor material is mixed with the silicon-containing alumina through the calcination of the polyimide to form a metal-semiconductor heterojunction, which improves metal dispersion and weakens the adsorption and bonding effect between the metal and the support.
A uniform dispersion of high metal loads is achieved, and the mechanical strength and catalytic activity of the catalyst are improved, especially in the hydrotreatment of residue oil, which shows excellent desulfurization, denitrification, deresolvation and demetalization properties.
Smart Images

Figure BDA0003616451840000071 
Figure BDA0003616451840000072 
Figure BDA0003616451840000081
Abstract
Description
Technical Field
[0001] The present invention relates to a hydrogenation catalyst and a preparation method and application thereof, and in particular to a hydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] Residue oil hydrogenation catalysts are mainly metal-supported catalysts, mostly with alumina and / or silica as carriers, and Ni, Mo, Co, etc. as active metal components. In the existing methods, when the active metal loading is large, metal particles tend to agglomerate or be unevenly distributed. In addition, during the calcination process, due to the strong interaction between the metal and the carrier, metal-oxygen-aluminum bonds are formed, which affects the catalytic efficiency of the catalyst and ultimately leads to a decrease in the hydrogenation activity of the catalyst. Introducing an appropriate amount of silicon oxide into the alumina carrier is beneficial to improving the acidity and specific surface area of alumina, which is beneficial to polymerization and hydrogenation reactions.
[0003] CN103055908A discloses a method for preparing a hydroprocessing catalyst. The method firstly pulps aluminum hydroxide or aluminum oxide to form a slurry, adds concentrated phosphoric acid to react and obtains a sol; then uses the sol as a binder, kneads with macroporous aluminum oxide and microporous aluminum oxide, forms, dries and roasts to obtain an aluminum oxide carrier; then uses an active metal component impregnation solution to impregnate the aluminum oxide carrier, and dries and roasts to obtain a hydroprocessing catalyst. The method is complicated to operate, the introduction of acidic sites will promote the bonding between the active metal and the carrier, the use of a large amount of concentrated acid will cause environmental pollution, and industrial production is relatively dangerous.
[0004] CN105582945A discloses a method for preparing a hydroprocessing catalyst. The method is to first impregnate an alumina carrier with a urea aqueous solution, then spray an aqueous solution of a polyol or a monosaccharide on the alumina carrier in a descending order of concentration, so that the concentration of the polyol and / or the monosaccharide forms a gradient distribution from low to high from the outside to the inside on the carrier, and then load the active metal component. This method requires multiple steps of spraying and impregnation to form a polymer carbonized shell layer, and has a high requirement for the solution concentration, and the actual operation process is relatively complicated.
[0005] CN1257754A discloses a method for preparing a silica-alumina catalyst carrier, wherein a silica-alumina precursor is prepared by introducing water glass and aluminum sulfate, and the prepared carrier has a pore volume of 0.45-0.75 mL / g and an average pore size of 5-10 nm. However, the final synthesized silica-alumina carrier has a small pore size and is not suitable for use as a hydrogenation catalyst for heavy oil or residual oil with a large molecular weight.
[0006] CN1169614C discloses a method for preparing silicon-containing aluminum hydroxide. By introducing a certain amount of sodium silicate in the process of preparing aluminum hydroxide gel by carbonization, and continuing to add a certain amount of sodium silicate in the subsequent aging process, silicon-containing aluminum hydroxide can be prepared. The average pore size is small. Although it is suitable for heavy oil or residual oil hydrodesulfurization or hydrodenitrogenation catalysts, for residual oil hydrodemetallization catalysts, its pore size is small and needs further improvement. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a hydrogenation catalyst and a preparation method and application thereof. The catalyst provided by the present invention has a high metal loading, is evenly dispersed, has high mechanical strength, has suitable pore distribution and specific surface area, and has suitable surface acidity, and is suitable for residual oil hydrogenation treatment.
[0008] The first aspect of the present invention provides a hydrogenation catalyst, comprising a polyimide / silicon-containing alumina composite carrier and an active metal, wherein the mass ratio of polyimide to silicon-containing alumina in the composite carrier is 0.05-0.40, and the mass content of silicon oxide in the silicon-containing alumina is 5%-40%, preferably 9.5%-17.0%.
[0009] In the present invention, in the catalyst, the active metal is at least one of the VIB group metals and at least one of the VIII group metals, wherein the VIB group metal is preferably at least one of Mo and W, more preferably Mo, and the VIII group metal is preferably at least one of Co and Ni, more preferably Ni.
[0010] In the present invention, in the catalyst, based on the mass of the catalyst, the content of the metal oxide of group VIB is 15% to 25%, and the content of the metal oxide of group VIII is 1.9% to 5.6%.
[0011] In the present invention, in the catalyst, the active metal dispersion is: VIB / I Al (×100) is 2 to 6, I VIII / I Al (×100) is 1 to 8.
[0012] In the present invention, the specific surface area of the catalyst is 110 to 245 m 2 / g, preferably 195 to 225 m 2 / g, pore volume is 0.4~1.2cm 3 / g, the mechanical strength is 16-26N / mm, preferably 19-24N / mm, the pore volume of pores with a pore diameter of 15-80nm accounts for 3%-20% of the total pore volume, and the pore volume of pores with a pore diameter of less than 8nm accounts for less than 7% of the total pore volume, preferably 3%-6%.
[0013] In the present invention, the acid content of the catalyst is 0.3 to 0.9 mmol / g, preferably 0.4 to 0.75 mmol / g. The ratio of the acid content of B acid to the acid content of L acid is C B / C L It is 0.02 to 0.09, preferably 0.055 to 0.088.
[0014] The second aspect of the present invention provides a method for preparing the above-mentioned hydrogenation catalyst, comprising the following steps:
[0015] (1) preparing polyimide material;
[0016] (2) preparing a silicon-containing pseudo-boehmite wet filter cake, and drying the wet cake to obtain silicon-containing pseudo-boehmite;
[0017] (3) mixing the polyimide material obtained in step (1) with the silicon-containing pseudo-boehmite obtained in step (2), forming, and drying to obtain a polyimide / silicon-containing alumina composite carrier;
[0018] (4) The composite support prepared in step (3) is mixed with the metal solution C for saturation impregnation, dried, and calcined under an inert atmosphere to obtain the catalyst.
[0019] In the method of the present invention, in step (2), the method for preparing a silicon-containing pseudo-boehmite wet filter cake comprises:
[0020] (A) adding a first alkaline solution into a first reaction kettle, introducing a mixed gas containing carbon dioxide to react, and making the pH value of the system be 2 to 4;
[0021] (B) adding bottom water to the second reaction kettle, heating to the reaction temperature, and then adding the second alkaline solution and the material obtained in step (A) into the second reaction kettle in parallel to react;
[0022] (C) aging the slurry obtained after the reaction in step (B), filtering and washing after the aging to obtain a silicon-containing pseudo-boehmite filter cake.
[0023] In the method of the present invention, in step (A), the first alkaline solution is one or both of a sodium aluminate solution and a potassium aluminate solution, preferably a sodium aluminate solution; the concentration of the sodium aluminate solution and / or potassium aluminate is 10 to 30 g Al2O3 / L in terms of Al2O3, and the caustic ratio of the first alkaline solution is 1.35 to 1.65.
[0024] In the method of the present invention, in step (A), the volume of the first alkaline solution added to the first reactor is 2 / 3 to 3 / 4 of the volume of the first reactor; the volume fraction of carbon dioxide in the carbon dioxide-containing mixed gas is 30% to 70%; the carbon dioxide-containing mixed gas can be a mixed gas of carbon dioxide and air.
[0025] In the method of the present invention, in step (A), the initial reaction temperature for the reaction of the mixed gas containing carbon dioxide is 15 to 65°C. The reaction is an exothermic reaction, and the system temperature gradually increases. The entire reaction process does not require cooling to maintain a low temperature. Generally, the temperature of the slurry at the end of the reaction is 40 to 75°C.
[0026] In the method of the present invention, in step (B), the second alkaline solution is a mixed solution of water glass and an aluminum-containing alkaline solution; the aluminum-containing alkaline solution is one or both of a sodium aluminate solution or a potassium aluminate solution, preferably a sodium aluminate solution. The modulus of the water glass is 2.5 to 3.0, and the caustic ratio of the sodium aluminate solution or the potassium aluminate solution is 1.10 to 1.40, preferably 1.15 to 1.35.
[0027] In the method of the present invention, in step (B), the concentration of water glass in the second alkaline solution is 5 to 95 g SiO2 / L in terms of SiO2, and the concentration of sodium aluminate and / or potassium aluminate in the second alkaline solution is 130 to 350 g Al2O3 / L in terms of Al2O3, preferably 150 to 250 g Al2O3 / L.
[0028] In the method of the present invention, in step (B), the bottom water added to the second reaction kettle is 1 / 10 to 1 / 5 of the volume of the second reaction kettle.
[0029] In the method of the present invention, in step (B), the material obtained in step (A) is added to the second reactor, and the material addition time is controlled to be 60 to 150 minutes. Further, in step (B), the second alkaline solution and the material obtained in step (A) are added to the second reactor in parallel to react, and the pH value is controlled to be 7.5 to 9.0.
[0030] In the method of the present invention, in step (B), the reaction temperature of the reaction is 40°C to 70°C, preferably 45°C to 65°C.
[0031] In the method of the present invention, in step (B), the reaction is carried out under stirring.
[0032] In the method of the present invention, in step (C), the aging conditions are: temperature of 50° C. to 95° C., and time of 30 min to 20 min.
[0033] In the method of the present invention, in step (C), the washing can be carried out by conventional washing methods in the art, preferably by washing with deionized water at 50° C. to 80° C. until the mixture becomes neutral.
[0034] In the method of the present invention, in step (C), the solid content of the obtained silicon-containing pseudo-boehmite wet filter cake is 35wt% to 45wt%.
[0035] Furthermore, in step (1), the synthesis of the polyimide material comprises:
[0036] (a) dissolving p-diaminobenzene in N,N-dimethylformamide solution, then adding pyromellitic dianhydride, stirring, to obtain a viscous solution;
[0037] (b) transferring the above solution into a reaction vessel, heating for reaction, cooling, washing with an organic solvent, drying, and grinding;
[0038] (c) calcining the obtained powder sample under the protection of an inert gas to obtain the polyimide material.
[0039] In the method of the present invention, in step (a), the concentration of p-diaminobenzene in the N,N-dimethylformamide solution is 0.005-0.1 g / mL, preferably 0.01-0.05 g / mL.
[0040] In the method of the present invention, in step (a), the concentration of pyromellitic dianhydride in N,N-dimethylformamide solution is 0.01-0.2 g / mL, preferably 0.02-0.1 g / mL.
[0041] In the method of the present invention, in step (a), the stirring time is 2 to 24 hours, preferably 6 to 10 hours.
[0042] In the method of the present invention, in step (b), the heating temperature is 130 to 300° C., preferably 160 to 190° C., and the time is 4 to 15 hours.
[0043] In the method of the present invention, in step (b), the organic solvent is one of N,N-dimethylformamide or toluene, preferably N,N-dimethylformamide, and the washing times are 2 to 6 times.
[0044] In the method of the present invention, in step (b), the drying temperature is 100-120° C. and the drying time is 2-5 hours.
[0045] In the method of the present invention, in step (c), the inert atmosphere is selected from at least one of Ar, He, and N2; the calcination temperature is 250 to 600°C, preferably 300 to 400°C, and the calcination time is 4 to 15 hours.
[0046] In the method of the present invention, in step (2), the drying temperature is 60-150° C., and the drying time is 4-10 hours. The dry basis content of the pseudo-boehmite obtained after drying is 75wt%-85wt%.
[0047] In the method of the present invention, in step (3), the mass ratio of the polyimide material obtained in step (1) to the silicon-containing pseudo-boehmite is 0.05 to 0.30. The molding can be performed by extrusion molding. An extrusion aid can be added during the molding process, and the extrusion aid can be sesbania powder, and the amount of the extrusion aid added is 1% to 6% of the mass of the silicon-containing pseudo-boehmite.
[0048] In the method of the present invention, in step (3), the drying temperature is 80 to 120° C. and the drying time is 4 to 6 hours.
[0049] In the method of the present invention, in step (4), the impregnation is performed by saturated impregnation; the active metal in the active metal solution C is selected from at least one of the VIB group metals and at least one of the VIII group metals, wherein the VIB group metal is preferably at least one of Mo and W, more preferably Mo, and the VIII group metal is preferably at least one of Co and Ni, more preferably Ni, wherein the concentration of the VIB group metal in terms of oxide is 0.15 to 0.4 g / mL, and the concentration of the VIII group metal in terms of oxide is 0.02 to 0.09 g / mL.
[0050] In the method of the present invention, in step (4), the drying temperature is 80-120°C, the drying time is 2-5 hours, the roasting temperature is 600-900°C, the roasting time is controlled at 3-5 hours, and the roasting is carried out in an inert atmosphere (such as N2).
[0051] The third aspect of the present invention provides the use of the above hydrogenation catalyst in a residue oil hydrogenation process.
[0052] In the present invention, residual oil and hydrogen-containing gas are contacted and reacted under hydrogenation reaction conditions in the presence of the above hydrogenation catalyst or the hydrogenation catalyst obtained according to the above preparation method.
[0053] In the above-mentioned residue oil hydrogenation reaction, the residue oil material is selected from one of atmospheric residue oil, vacuum residue oil and high-temperature coal tar.
[0054] In the above-mentioned residue oil hydrogenation reaction, the hydrogen-containing gas is hydrogen, or a mixture of hydrogen and other gases. The volume content of hydrogen in the mixture is generally not less than 80%, preferably not less than 85%, and more preferably not less than 95%.
[0055] In the above-mentioned residue oil hydrogenation process, the operating conditions of the residue oil hydrogenation are as follows: reaction pressure is 5-20 MPaG, reaction temperature is 280-400°C, liquid hourly volume space velocity is 0.1-3.0 h-11 , the volume ratio of hydrogen to oil is 100-1000.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] The hydrogenation catalyst provided by the present invention has uniform dispersion of active metals, high mechanical strength, suitable pore distribution and specific surface area, suitable surface acidity, is applied to residual oil hydrogenation treatment, has good desulfurization, denitrification and residual carbon removal performance, and especially shows more excellent catalytic performance in demetallization.
[0058] In the preparation method of the catalyst of the present invention, the high molecular polymer polyimide contains C, N, and O elements. After calcination, the band gap of the organic carbon material is opened to become a semiconductor material, which is then mixed with silicon-containing pseudo-boehmite, and impregnated with a metal solution after extrusion molding. Since a metal-semiconductor heterojunction is formed on the contact interface between the active phase metal and the polyimide, the heterojunction will accelerate the migration rate of electrons between the active metal and the polyimide, and at the same time, the interaction force between the two is enhanced, so the active metal will be more inclined to be loaded on the polyimide surface during the loading process, effectively improving the metal dispersibility, and can greatly weaken the adsorption and bonding between the active metal and the silicon-containing alumina carrier. The synthesized catalyst is more active in the residual oil hydrogenation process. Further, the band gap size can be adjusted by adjusting the polyimide calcination temperature, thereby adjusting the size of the interaction force between the active metal and the polyimide. In the subsequent calcination process, the nitrogen element contained in the polyimide can play a role in adjusting the surface acidity of the catalyst. In addition, the silicon-containing pseudo-boehmite wet filter cake prepared by the present invention has low gibbsite content, high crystallinity, and easily adjustable silicon content, and the silicon-containing alumina obtained by calcination has a large pore volume and pore diameter; at the same time, the silicon-containing pseudo-boehmite wet filter cake prepared by the present invention has a high peptization index, which provides a guarantee for preparing a carrier with high lateral compression strength. DETAILED DESCRIPTION
[0059] In the present invention, the ASAP2020 fully automatic physical adsorption instrument produced by Micromeritics Corporation of the United States is used to test the nitrogen adsorption-desorption curve of the sample at -196°C to determine the specific surface area, pore volume and pore size distribution.
[0060] In the present invention, the mechanical strength is tested by using a ZQJ-Ⅲ intelligent particle strength testing machine manufactured by Dalian Zhiqu Testing Machine Factory to measure the average mechanical strength of a group of samples with a length of 4-6 mm.
[0061] In the present invention, the metal dispersion is measured by XRS (the instrument is Kratos Axis Ultra DLD model) to measure the XPS peak intensity ratio of active metals and aluminum element.
[0062] In the present invention, the infrared acid content is measured using a Nicolet 870 Fourier transform infrared spectrometer produced by Nicolet Company of the United States.
[0063] The technical solutions and effects of the present invention are further described below in conjunction with embodiments, but are not limited to the following embodiments.
[0064] Example 1
[0065] (1) A sodium aluminate mixed solution with a caustic ratio of 1.45 and a concentration of 25 g Al2O3 / L was added to a 5000 mL first reaction kettle, and then a mixed gas of carbon dioxide and air containing 55% carbon dioxide by volume was introduced to reduce the pH value of the system to 3.4. The temperature of the material at the end of the reaction was 55°C;
[0066] 1500 mL of bottom water was added to a 10000 mL second reaction kettle, and a stirring and heating device was started. When the temperature rose to 65° C., the above materials were added to the second reaction kettle at a flow rate of 35 mL / min for 90 min, and 3500 mL of water glass with a modulus of 2.8 and a concentration of 50 g SiO2 / L and a sodium aluminate solution with a concentration of 180 gAl2O3 / L and a caustic ratio of 1.25 were added in parallel. The pH value of the slurry in the second reaction kettle was controlled to be 8.0 by adjusting the flow rate of the sodium aluminate solution, and the temperature of the slurry in the second reaction kettle was kept constant. After the above materials were used up, the reaction was terminated, and the slurry was aged at 90° C. for 80 min. After the aging was completed, the slurry was washed with deionized water at a temperature of 70° C. until it was neutral, and filtered to obtain a silicon-containing pseudo-boehmite wet cake with a solid content of 42%, which was then dried at 120° C. for 6 hours to obtain the silicon-containing pseudo-boehmite required by the present invention.
[0067] (2) Dissolve 100 mmol of p-diaminobenzene in 60 mL of N,N-dimethylformamide solution, add 2.2 g of pyromellitic anhydride, and stir rapidly for 8 h until the solution becomes viscous. Then transfer the above solution to a hydrothermal reactor, heat it at 180 ° C for 10 h, and after cooling, rinse it with N,N-dimethylformamide solvent 3 times, dry it at 110 ° C for 4 h, and grind it for use. The powder sample is calcined under nitrogen protection for 8 h at a calcination temperature of 350 ° C to obtain a polyimide carrier.
[0068] (3) Weigh 100 g of a polyimide sample, 500 g of siliceous pseudo-boehmite (dry basis content 80%), and 15 g of sesbania powder, mix and extrude into strips, and dry at 120° C. for 4 hours to obtain a composite carrier.
[0069] (4) An impregnation solution containing 0.280 g / mL MoO3 and 0.077 g / mL NiO was prepared and the composite support was saturated with the solution. After the impregnation was complete, the solution was dried at 120°C for 5 hours and calcined at 650°C for 3 hours under nitrogen protection to obtain a final hydrogenation catalyst A. The physicochemical properties of the catalyst are shown in Table 1.
[0070] Example 2
[0071] Its synthesis process is the same as that of Example 1, except that the amount of polyimide added is changed to 150 g, to obtain the final hydrogenation catalyst B, whose physicochemical properties are shown in Table 1.
[0072] Example 3
[0073] The other synthesis processes were the same as those in Example 1, except that the concentration of SiO2 in the mixed solution in the preparation of pseudo-boehmite in step (1) was changed to 75 g / L, the concentration of Al2O3 in the first reaction kettle was changed to 15 g / L, the volume fraction of carbon dioxide in the mixed gas of carbon dioxide and air used was 45%, and the aging temperature was changed to 95°C to obtain the silicon-containing pseudo-boehmite required in this example. The final hydrogenation catalyst C was obtained, and its physicochemical properties are shown in Table 1.
[0074] Example 4
[0075] The other synthesis process is the same as that of Example 1, except that in step (3), 40 g of polyimide sample is weighed, mixed with 500 g of silicon-containing pseudo-boehmite (dry basis content 80%) and 15 g of sesbania powder and then extruded. The final hydrogenation catalyst D obtained has its physicochemical properties shown in Table 1.
[0076] Comparative Example 1
[0077] The other synthesis processes were the same as in Example 1, except that the polyimide was replaced by an equal amount of activated carbon powder to obtain the final hydrogenation catalyst E, whose physicochemical properties are shown in Table 1.
[0078] Comparative Example 2
[0079] The other synthetic processes are the same as those of Example 1, except that the preparation process of pseudo-boehmite in step (1) is different, that is, 3000 mL of sodium aluminate solution with a concentration of 65 gAl2O3 / L and a caustic ratio of 1.35 is added to a 5.0 L reactor, and then a mixture of carbon dioxide and air with a carbon dioxide content of 80% (volume fraction) is introduced, the initial reaction temperature is 25°C, the slurry temperature is maintained constant by cooling, and the reaction time is controlled to be 45 min, so that the pH value of the sodium aluminate solution is reduced to 8.8. The slurry is filtered, washed with 75°C deionized water, and dried at 120°C for 6 hours after washing to obtain pseudo-boehmite. The final hydrogenation catalyst F is obtained, and its physicochemical properties are shown in Table 1.
[0080] Example 5
[0081] The catalysts obtained in Examples 1-4 and Comparative Examples 1-2 were used in residual oil hydrogenation reactions. The properties of the raw materials are shown in Table 2, and the evaluation conditions and results are shown in Table 3.
[0082] Table 1 Physicochemical properties of hydrogenation catalysts
[0083]
[0084] Table 2 Raw oil properties
[0085]
[0086]
[0087] Table 3 Evaluation conditions and evaluation results of the hydrogenation catalysts obtained in each example
[0088]
Claims
1. A hydrogenation catalyst comprising a polyimide / silicon-containing alumina composite carrier and an active metal, wherein: The mass ratio of polyimide to silicon-containing alumina in the composite carrier is 0.05-0.40, and the mass content of silicon oxide in the silicon-containing alumina is 5%-40%; the active metal is at least one of the metals of Group VIB and at least one of the metals of Group VIII; in the catalyst, based on the mass of the catalyst, the content of the metal oxide of Group VIB is 15%-25%, and the content of the metal oxide of Group VIII is 1.9%-5.6%; in the catalyst, the dispersion degree of the active metal is: I VIB / I Al 0.02~0.06, I VIII / I Al is 0.01~0.08; the ratio of the acid content of B to the acid content of L is C B / C L It is 0.055~0.
088.
2. The catalyst according to claim 1, characterized in that In the composite carrier, the mass content of silicon oxide in silicon-containing alumina is 9.5% to 17.0%.
3. The catalyst according to claim 1, characterized in that The Group VIB metal is at least one of Mo and W, and the Group VIII metal is at least one of Co and Ni.
4. The catalyst according to claim 1, characterized in that The Group VIB metal is Mo and the Group VIII metal is Ni.
5. The catalyst according to claim 1, characterized in that The specific surface area of the catalyst is 110~245m 2 / g, pore volume is 0.4~1.2cm 3 / g, the mechanical strength is 16~26N / mm, the pore volume of pores with a pore diameter of 15~80nm accounts for 3%~20% of the total pore volume, and the pore volume of pores with a pore diameter of less than 8nm accounts for less than 7% of the total pore volume.
6. The catalyst according to claim 1, characterized in that The specific surface area of the catalyst is 195-225 m 2 / g, pore volume is 0.4~1.2cm 3 / g, the mechanical strength is 19~24N / mm, the pore volume of pores with a pore diameter of 15~80nm accounts for 3%~20% of the total pore volume, and the pore volume of pores with a pore diameter of less than 8nm accounts for 3%~6% of the total pore volume.
7. The catalyst according to claim 1, characterized in that The acid amount of the catalyst is 0.3-0.9 mmol / g.
8. The catalyst according to claim 1, characterized in that The acid amount of the catalyst is 0.40-0.75 mmol / g.
9. A method for preparing the catalyst according to any one of claims 1 to 8, comprising the steps of: (1) Preparation of polyimide materials; (2) preparing a silicon-containing pseudo-boehmite wet filter cake, and drying the wet cake to obtain silicon-containing pseudo-boehmite; (3) mixing the polyimide material obtained in step (1) with the silicon-containing pseudo-boehmite obtained in step (2), forming, and drying to obtain a polyimide / silicon-containing alumina composite carrier; (4) mixing the composite support prepared in step (3) with the metal solution C for saturated impregnation, drying, and calcining under an inert atmosphere to prepare the catalyst; The synthesis of the polyimide material in step (1) comprises: (a) dissolving p-diaminobenzene in N,N-dimethylformamide solution, then adding pyromellitic dianhydride and stirring to obtain a viscous solution; (b) transferring the above solution into a reaction vessel, heating for reaction, cooling, washing with an organic solvent for several times, drying, and grinding; (c) calcining the obtained powder sample under the protection of an inert gas to obtain the polyimide material.
10. The preparation method according to claim 9, characterized in that: The method for preparing a silicon-containing pseudo-boehmite wet filter cake in step (2) comprises: (A) adding a first alkaline solution into a first reaction kettle, introducing a mixed gas containing carbon dioxide to react, and making the pH value of the system be 2-4; (B) adding bottom water to the second reaction kettle, heating to the reaction temperature, and then adding the second alkaline solution and the material obtained in step (A) into the second reaction kettle in parallel to react; (C) aging the slurry obtained after the reaction in step (B), filtering and washing after the aging to obtain a filter cake containing silicon-containing pseudo-boehmite.
11. The preparation method according to claim 9, characterized in that: In step (3), the mass ratio of the polyimide material to the silicon-containing pseudo-boehmite is 0.05-0.
30.
12. The preparation method according to claim 9, characterized in that: In step (4), the impregnation is performed by saturated impregnation; the active metal in the active metal solution C is selected from at least one of the metals of Group VIB and at least one of the metals of Group VIII, wherein the concentration of the metal of Group VIB as oxide is 0.15-0.4 g / mL, and the concentration of the metal of Group VIII as oxide is 0.02-0.09 g / mL.
13. The preparation method according to claim 12, characterized in that: The Group VIB metal is at least one of Mo and W, and the Group VIII metal is at least one of Co and Ni.
14. The preparation method according to claim 12, characterized in that: The Group VIB metal is Mo and the Group VIII metal is Ni.
15. The preparation method according to claim 9, characterized in that: In step (4), the calcination temperature is 600-900° C., the calcination time is controlled at 3-5 hours, and the calcination is carried out in an inert atmosphere.
16. Use of the hydrogenation catalyst according to any one of claims 1 to 8 in a residue oil hydrogenation process.
Citation Information
Patent Citations
Preparation method of hydrotreating catalyst
CN103055908A
Preparation method of hydrogenation treatment catalyst
CN105582945A
Hydrogenation deoxidation catalyst and preparation method thereof
CN104888766A